An Economic Model of Optimal Penalty for Health Care Workplace Violence - Zesheng Sun PhD; Sharon X. Lin PhD; Shuhong Wang PhD (SAGE Publishing, 2019)
This article provides an economic model on the optimal penalty of health care workplace violence based on health care workplace classification and cost structure, aiming to deter potential offenders. By developing an EIP (externality, identifiability, and preventability) analytical method, we distinguish the characteristics of different workplaces and find that the health care workplace is the combination of externality, low identifiability, and low preventability. Besides the private cost to victims for ordinary workplace violence, the cost structure of health care workplace violence includes social costs like externality-related public safety cost, defensive medicine cost, and specific factors cost. When the optimal penalty corresponding to different levels of health care workplace violence increases, the threshold level of punishable violence decreases after incorporating the social costs into analysis. Our model shows that public safety costs are positively correlated with the importance of health care workplace in the service network, and a higher public safety cost should be matched with a greater optimal penalty.